Pharmaceutical Cocrystals: An Overview - Jagdish Kumar Rawal; Dr. Anshu Sharma (Asian Journal of Pharmaceutical Research and Development, 2025)
Poor aqueous solubility and low oral bioavailability of an active pharmaceutical ingredient are the major constraints during the development of new product. Various approaches have been used for enhancement of solubility of poorly aqueous soluble drugs, but success of these approaches depends on physical and chemical nature of molecules being developed. Cocrystallization of drug substances offers a great opportunity for the development of new drug products with superior physicochemical such as melting point, tabletability, solubility, stability, bioavailability and permeability, while preserving the pharmacological properties of the active pharmaceutical ingredient. Cocrystals are multicomponent systems in which two components, an active pharmaceutical ingredient and a coformer were present in stoichiometric ratio and bonded together with non-covalent interactions in the crystal lattice. This review article presents a systematic overview of pharmaceutical cocrystals. Differences between cocrystals with salts, solvates and hydrates are summarized along with the advantages of cocrystals with examples. The theoretical parameters underlying the selection of coformers and screening of cocrystals have been summarized and different methods of cocrystal formation and evaluation have been explained.